2015
DOI: 10.1139/cjpp-2015-0003
|View full text |Cite
|
Sign up to set email alerts
|

TIIA attenuates LPS-induced mouse endometritis by suppressing the NF-κB signaling pathway

Abstract: Endometritis is one of the main diseases that harms the dairy cow industry. Tanshinone IIA (TIIA), a fat-soluble alkaloid isolated from Salviae miltiorrhizae, has been reported to have potent anti-inflammatory properties. However, the anti-inflammatory effects of TIIA on a mouse model of lipopolysaccharide (LPS)-induced endometritis remain to be elucidated. The purpose of the present study was to investigate the effects of TIIA on LPS-induced mouse endometritis. TIIA was intraperitoneally injected 1 h before a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 37 publications
1
32
0
Order By: Relevance
“…Recently, study also showed the infiltration of neutrophils into the endometrium of mice with lipopolysaccharides (LPS)-induced endometritis [34]. When mass neutrophils reach the tissue at the site of infection, they will release abundant inflammatory factors, oxygen free radical and proteolytic enzyme to kill pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, study also showed the infiltration of neutrophils into the endometrium of mice with lipopolysaccharides (LPS)-induced endometritis [34]. When mass neutrophils reach the tissue at the site of infection, they will release abundant inflammatory factors, oxygen free radical and proteolytic enzyme to kill pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, isolating and developing naturally occurring monomers from medicinal plants have become resurgence of interest (Zheng et al, 2010 ). Furthermore, numerous Chinese herbal medicines have been widely used in clinical case, which are useful to treat inflammatory diseases, including mastitis, acute lung injury and endometritis (Lv et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Sodium tanshinone IIA sulfonate (STS, molecular structure shown in Wu et al 2009), inhibit inflammatory response (Li et al 2015;Lu et al 2016;Yang et al 2016) and prevent atherosclerosis (Chang et al 2014;Chen et al 2012;Chen and Xu 2014;Fang et al 2008) as well as cardiac injury (Gao et al 2012;Jiang et al 2009) and hypertrophy (Feng and Zheng 2008;Weng et al 2015;Yang et al 2007). Tanshinone IIA has also been reported to prevent LPS-induced inflammation response in acute lung injury (Xu et al 2015) and in RAW264.7 macrophages (Fan et al 2016;Jang et al 2006) via inhibition of the NF-κB pathway.…”
Section: Introductionmentioning
confidence: 99%